2015
DOI: 10.5194/bg-12-3403-2015
|View full text |Cite
|
Sign up to set email alerts
|

Differences in microbial community composition between injection and production water samples of water flooding petroleum reservoirs

Abstract: Abstract. Microbial communities in injected water are expected to have significant influence on those of reservoir strata in long-term water flooding petroleum reservoirs. To investigate the similarities and differences in microbial communities in injected water and reservoir strata, high-throughput sequencing of microbial partial 16S rRNA of the water samples collected from the wellhead and downhole of injection wells, and from production wells in a homogeneous sandstone reservoir and a heterogeneous conglome… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 27 publications
0
22
1
1
Order By: Relevance
“…As a result, we found that even in the same reservoir block, only a small number of microbial organisms were observed across the water samples from different production wells in the same reservoir. This phenomenon has also been documented by analysing the microbial communities derived from the wellhead and downhole of injection wells, and from their effective production wells nearby 20 .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…As a result, we found that even in the same reservoir block, only a small number of microbial organisms were observed across the water samples from different production wells in the same reservoir. This phenomenon has also been documented by analysing the microbial communities derived from the wellhead and downhole of injection wells, and from their effective production wells nearby 20 .…”
Section: Discussionmentioning
confidence: 93%
“…Diverse microbial community structures in the production wells from the same reservoir were also observed. The differences observed may be related to the isolation of the oil-bearing strata, the depth span of the reservoir strata 1 20 23 , and/or stochastic processes 28 54 . The spatial isolation and low permeability of reservoir strata may exert a significant influence on the community composition and structure in oil wells, even those located the same reservoir block.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Petroleum reservoirs represent special environments underground with low permeability. Owing to the sieve effect on microbial cells when injected fluid passes through a subsurface formation, the injected exogenous microorganisms may not migrate into the reservoir formation ( Youssef et al, 2009 ; Gao et al, 2015a ; Ren et al, 2015 ). Youssef et al (2007) injected B. licheniformis , B. subtilis subsp.…”
Section: Discussionmentioning
confidence: 99%
“…The drawback is that these microorganisms must be able to grow in the presence of competing indigenous populations ( Bryant, 1991 ). Furthermore, because of the sieve effect of strata on microbial cells, the injected microorganisms are generally difficult to migrate into reservoir strata to reach the production wells ( Youssef et al, 2009 ; Gao et al, 2015a ; Ren et al, 2015 ). Indigenous microbial flooding is another promising oil-recovery technique that has been successfully applied in the petroleum industry ( Belyaev et al, 1998 ; Liu et al, 2005 ; Li et al, 2014 ; Wang et al, 2014b ; Le et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%